Modelagem computacional de chaminés de equilíbrio e tanques de alimentação unidirecional como dispositivos atenuadores do golpe de aríete em adutoras - Barbosa, Marcus Paulo Rosa (2006)
The main goal of this research is the development of the computer code designed to model the water hammer problem which occurs in water pipes. It was used the method of characteristics to numerically solve the differential equations which control the problem. The software developed allows the user to visualize the behavior oh the over and under pressure waves resulting from the occurrence of the transient problem. Other features of the developed software includes the possibility of analyzing the introduction of mechanisms to decrease the effects of the water hammer problem such as orifice tanks, one-way tanks, closed tanks and relief valves. The developed model was applied and validated to water conducts which was previously been analyzed by the software CTran, developed by the “Escola Politécnica de Universidade de São Paulo”. The results were very satisfactory